IMPLEMENTASI PENDIDIKAN ANTIKORUPSI DI SEKOLAH - Ahmad Ansyari Siregar; Ika Chastanti (IKIP PGRI Pontianak, 2022)
Corruption is an extraordinary crime (Eradication of corruption is not enough to be overcome by relying only on the process of law enforcement but preventive measures need to be taken by instilling anti-corruption values in schools. The purpose of this study was to determine the implementation of anti-corruption education in schools, the learning strategies used by teachers in the learning process, and the obstacles experienced by schools in their implementation. This research is a qualitative research with a descriptive delivery. Data is collected by In-depth Interview of the school principal, teacher, and students. Data analysis techniques were performed using the Miles and Huberman Models. The results show that the implementation of anti-corruption education has not been done in schools where teachers have not integrated anti-corruption behavior in the learning process. Teachers have not been able to set an example for students and teachers have not been able to implement learning strategies to increase student interest and motivation to reduce corrupt behavior.